A ball mill‐assisted vortex‐enhanced matrix solid‐phase dispersion method for the extraction and determination of five phenolic compounds from Rubi Fructus by high‐performance liquid chromatography. Issue 5 (13th March 2021) - Yan, Chaozhuo; Zhang, Yaqian; Du, Kunze; Guo, Jiading; He, Jun; Li, Jin; Chang, Yan‐xu
Abstract: Rubi Fructus, a common traditional Chinese medicine, is abundant in phenolic components with pharmacodynamical effect. An efficient and rapid ball mill‐assisted vortex‐enhanced matrix solid‐phase dispersion method was developed for the simultaneous quantification of five phenols (ellagic acid, kaempferol‐3‐ O ‐rutinoside, astragalin, tiliroside, and kaempferol) in Rubi Fructus by high‐performance liquid chromatography. The introduction of the ball mill instrument realized the automation of the first step of matrix solid‐phase dispersion. Several extraction parameters were evaluated, and the best extraction conditions were optimized by response surface methodology. The method exhibited a good linearity for the five compounds ( r 2  > 0.999). The recoveries of the five target analytes in Rubi Fructus ranged from 98.7% to 102% (RSD≤3.92%) under the optimized conditions: Al‐SBA‐15 as a dispersant, sample/dispersant ratio of 1:3, ball milling time as 2 min, vibration frequency of the ball mill as 1300 rpm, 1.4 mL methanol as eluent and vortex time as 3 min. Consequently, the established ball mill‐assisted vortex‐enhanced matrix solid‐phase dispersion combined with HPLC could be applied to extract and analyze the target phenolic compounds in Rubi Fructus samples.